Cars 2 [videorecording (DVD)] - Lasseter, John; Lewis, Brad (Bradford); Queen, Ben; Wilson, Owen, 1968-; Larry, the Cable Guy; Caine, Michael; Mortimer, Emily; Turturro, John, 1957-; Izzard, Eddie (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2011)
Star racecar Lightning McQueen and the incomparable tow truck Mater take their friendship on the road from Radiator Springs to exciting new places when they head overseas to compete in the first-ever World Grand Prix to determine the world's fastest car. But the road to the championship is filled with plenty of potholes, detours, and hilarious surprises when Mater gets caught up in an intriguing adventure of his own: international espionage!